Leg electromyography and the VO2 -power relationship during bicycle ergometry - Bearden, S. E.; Moffatt, R. J. (Medicine & Science in Sports & Exercise, 2001)
PURPOSE: The relationship between oxygen consumption and power is not linear. The purpose of this investigation was to examine the nature of the relationship and the cause of the nonlinearity. METHODS: Eight male cyclists (60.5 +/- 3.8 mL O2.min-1.kg-1 VO2 peak) completed an incremental exercise test (1 W.5 s-1) to exhaustion. VO2 was measured every breath, and rmsEMG was recorded continuously over the belly of vastus lateralis, biceps femoris, and lateral gastrocnemius. RESULTS: VO2 is a linear function of power in moderate exercise; the slope of the linear portion was approximately 9.7 mL O2.min-1.W-1, which is consistent with the steady state gain for moderate exercise. Beyond this initial break from linearity, the VO2.W-1 plot demonstrates a second break that is not different from the point of respiratory compensation (break in VE.VCO2-1). These breaks were coincident with increased neuromuscular activity (1st break: 194 +/- 27 W for VO2, 191 +/- 25 W for vastus lateralis; 2nd break: 262 +/- 34 W for VO2, 258 +/- 27 W for vastus lateralis) and corresponded to approximately 58% VO2 peak for the first and 75% VO2 peak for the second break. CONCLUSIONS: VO2 is not a linear function of power. During an incremental test, neuromuscular activity and VO2 increase more rapidly in heavy exercise. Both VO2 and neuromuscular activity exhibit a second break at very high power output, which may mark an upper limit for sustainable exercise.